Plateletcrit as Risk Factor of Major Adverse Cardiac Event in Elderly Patient with Acute Coronary Syndrome - Kathrine, Anita Septiana Maria; Pramantara, I Dewa Putu; Hartopo, Anggoro Budi (Acta Interna The Journal of Internal Medicine, 2023)
Background. The morbidity and mortality of patients with acute coronary syndrome (ACS) are very high so it is important to do risk factor stratification. Several studies found that plateletcrit plays an important role in predicting mortality in STEMI patients and that it had a significant correlation as a predictor of a coronary slow flow phenomenon correlated with a worse cardiovascular outcome. The aging process is associated with altered platelet activity and a higher rate of vascular disease. The effect of aging on thrombotic function is not fully understood yet, so further research is needed. It is hypothesized that high plateletcrit increases the risk of major cardiovascular events (MACE) in elderly acute coronary syndrome (ACS) patients treated in intensive cardiac care unit (ICCU).Objective. To determine the role of plateletcrit as a risk factor for major cardiovascular events in elderly acute coronary syndrome patients.Method. We collected samples of elderly patients who experienced ACS in the period January 2016 - December 2019, recorded plateletcrit data and whether there were MACE incidents or not. The data were processed in SPSS to find a cut off of plateletcrit values which are a risk factor for the occurrence of MACE in elderly patients at Dr. Sardjito Hospital.Result. A total of 174 study subjects consisted of 58 MACE and 116 non-MACE groups, the results showed that platelecrit ≥0.35 increased the risk of MACE with a p value of 0.046 and OR 5.49.Conclusion. Plateletcrit is statistically significant to the incidence of MACE in elderly coronary syndrome patients who are treated in intensive cardiac are units.